2008
DOI: 10.1038/sj.eye.6703091
|View full text |Cite
|
Sign up to set email alerts
|

Identifying relationships between tomography-derived corneal thickness, curvature, and diameter and in vivo confocal microscopic assessment of the endothelium in healthy corneas of young adults

Abstract: Purpose Despite the importance of a healthy endothelial layer in anterior segment surgery, the possible influence of corneal parameters on endothelial cell density (ECD) has largely been ignored in the young adult eye. This study investigated the possible associations between corneal tomographic parameters and ECD values in young adults. Methods Subjects aged 21-30 years, with normal corneas were recruited. Mean ECD, mean cell area (MCA), coefficient of variation for cell area (COVA), and proportion of hexagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…A third and related possibility is that the En-DM complex response is more dynamic than the biphasic changes observed in other layers. Last, central corneal thickness has been found to be related to the endothelial cell density in young, normal subjects, 58 and there is a reduction in endothelial cell density with age. 53 It may be that the between-subject variability is due to different endothelial cell densities across the various subjects' ages in our sample, leading to a variation in the endothelial pump capacity across the sample.…”
Section: Discussionmentioning
confidence: 95%
“…A third and related possibility is that the En-DM complex response is more dynamic than the biphasic changes observed in other layers. Last, central corneal thickness has been found to be related to the endothelial cell density in young, normal subjects, 58 and there is a reduction in endothelial cell density with age. 53 It may be that the between-subject variability is due to different endothelial cell densities across the various subjects' ages in our sample, leading to a variation in the endothelial pump capacity across the sample.…”
Section: Discussionmentioning
confidence: 95%
“…Referring to theory based on histologic studies, the corneas of older people are thinner because of a reduction in keratocyte density and possible destruction of collagen fibers, and senior individuals are exposed to environmental factors for a longer period of time, which might influence corneal structure 38. Hasemian et al demonstrated that corneal endothelial cell density decreases in persons until 60 years of age; however, the volume of these cells increases 39.…”
Section: Discussionmentioning
confidence: 99%
“…Provided there are not too many errors, it should be fairly easy and not too time consuming to correct these cell border errors. 11,24,25,34 However, for the majority of grafts with non-uniform and large cells, this requires considerable time and is therefore largely impractical in a busy clinic. The automated option on the NAVIS software is substantially oversegmenting cell domains, thereby creating additional cell-cell borders at numerous locations across the ROI that are simply not present, resulting in an artificially high ECD.…”
Section: Discussionmentioning
confidence: 99%